CORRELATION OF ASPARTATE AMINOTRANSFERASE TO PLATELET RATIO INDEX (APRI) WITH THE DEGREE OF SEVERITY LIVER ORGAN IN CIRRHOSIS HEPATIC PATIENTS - mahendra aulia rakhman; Vitasari Indriani; Dwi Arini E (Fakultas Kedokteran Universitas Jenderal Soedirman, 2021)
Background: Cirrhosis hepatic is a chronic liver disease characterized by the replacement of liver tissue into scar tissue resulting in decreased liver function. The patient's diagnosis is gold standard for cirrhosis hepatic by invasive assessment cause tissue damage. The development of the way of diagnosis with secondary markers is APRI score was considered quite good in determining cirrhosis hepatic. On the other to, there is a method for assessing the severity of the liver organ in patients with cirrhosis hepatic using the Child-Pugh score. APRI scores and Child-Pugh scores are based on the calculation of secondary markers caused by hepatocyte cell fungtional damage. This is very useful in the early diagnosis of cirrhosis hepatic patients using simple markers and predicting the severity of the liver organ to assess further prognosis and management. Objective: To knowing the correlation of APRI index with the degree of severity liver organ in cirrhosis hepatic patients in RSUD Prof. dr. Margono Soekarjo. Specifically, it aims to determine the APRI score and Child-Pugh score in patients with cirrhosis hepatic. Methods: This study used a cross sectional design with a sample of 31 patients with a diagnosis of cirrhosis hepatic which was selected using a consecutive sampling technique. Primary data were obtained from a one-time blood sampling calculation and secondary data were obtained from medical records from patients with a diagnosis of liver cirrhosis from the physician in charge. Hypothesis analysis using Pearson correlation test. Resuls: Pearson test results showed a significant difference p = 0.024 (p <0.05) with the strength of the relationship r = 0.404 and the direction of a positive relationship on the correlation of APRI scores and Child-Pugh scores. Conclusions: There is a significant correlation between APRI scores with the degree of severity liver organ in cirrhosis hepatic patients in RSUD Prof. dr. Margono Soekarjo. The average APRI score in patients cirrhosis hepatic is 3, 107. The Child-Pugh score for the degree of severity liver organ is 8 or in the category of Child-Pugh B or moderate category.